(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
A series of the polysiloxanes modified with amino groups are synthesized. FTIR, 1HNMR are used to characterize the polysiloxane structure. Surface properties of the polysiloxane materials with amino groups are discussed. The results show that the polysiloxanes modified with tertiary amino groups had good flexibility and repellency to water. With increasing the amino value of the polysiloxanes, the flexibilities of the fabrics treated with the emulsion were improved. After the samples were treated with the polysiloxanes, the thermal yellowing had emerged. The whiteness of the fabrics treated with the polysiloxane decreased. The reflectance spectra of the fabrics treated without and with the modified polysiloxanes had not significant change.